FRENCH COLONIAL POLICY TOWARDS THE ENDOWMENTS OF THE TWO HOLY MOSQUES IN ALGERIA 1830 TO 1844 - مزوجي هشام; حيمر صالح (Journal of Human Sciences, 2022)
The Endowment of the Two Holy Mosques Endowments in Algeria at the end of the Ottoman era was ranked first in comparison to other charitable institutions, and this is due to the high status enjoyed by the sacred Bekaa in the hearts of Algerians, but the endowments of the Two Holy Mosques quickly recognized a great regression and decline in the beginning of the French occupation, and this What makes us wonder: What are the measures taken by the French colonial authorities towards the endowments of the Two Holy Mosques in Algeria? Since this study is historical, it was based on the historical approach through which we seek to identify the Foundation for the Endowments of the Two Holy Mosques, and the various measures taken by the French colonial administration towards this institution, and the most important results.